ZSM-23 molecular sieve as well as preparation method and application thereof
By using a combination of specific template agents and co-solvents and combining dynamic crystallization methods, ZSM-23 molecular sieve was prepared, which solved the shortcomings of ZSM-23 molecular sieve in the silicon-aluminum ratio, purity and pore properties in the prior art, and achieved more efficient catalytic performance and wider industrial applications.
Patent Information
- Application Number
- CN202411706839.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-25
AI Technical Summary
In the prior art, ZSM-23 molecular sieve is difficult to take into account the wide silicon-aluminum ratio range, high purity and good pore properties, resulting in insufficient catalytic activity and selectivity.
ZSM-23 molecular sieve was prepared by dynamic crystallization using specific types of template agents and co-solvents. The total template agent is a mixture of pyrrolidine and isopropylamine, or a combination of other template agents, and the co-solvents are ethanol, methanol, etc. By accurately controlling the molar ratio of the template agent and the co-solvent, the pore size and distribution are regulated, and the pore properties of the molecular sieve are optimized.
The scope of regulation of the silicon-aluminum ratio has been broadened, and the pore properties and catalytic properties of ZSM-23 molecular sieve have been significantly improved, providing a more efficient and stable catalyst selection.
Smart Images

Figure CN119683646A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of molecular sieves, and in particular to a ZSM-23 molecular sieve, a preparation method and application thereof. Background Art
[0002] ZSM-23 molecular sieve, as a member of the MTT configuration family, has a unique combination of five-membered rings, six-membered rings and teardrop-shaped ten-membered rings in its skeleton, which constructs a one-dimensional channel with a free diameter of 0.52×0.45nm. This tiny pore diameter feature, compared with ZSM-5 molecular sieve, gives ZSM-23 excellent selectivity in catalytic reactions, making it a preferred material in industrial catalytic processes such as methylation-alkylation cracking, octadecane skeleton isomerization, platinum-catalyzed hydrogenation isomerization, and n-hexane cracking to produce propylene.
[0003] Regarding the synthesis method of ZSM-23 molecular sieve, most of them adopt the hydrothermal method. For example, US4490342 discloses the synthesis conditions of preparing ZSM-23 using N,N-trimethylheptamine as a template, and the synthesis system is expanded in US4619820. US5707601 discloses a method for synthesizing ZSM-23 molecular sieve using small molecular amines and neutral amines.
[0004] However, the synthesis technology of ZSM-23 molecular sieve has obvious limitations. For example, the synthesis method using pyrrolidine as a template can produce ZSM-23 molecular sieve, but the resulting molecular sieve particles are large in size, which leads to poor diffusion performance. The lack of diffusion performance can easily lead to unnecessary secondary reactions, thereby reducing the catalytic activity and selectivity of the molecular sieve. Furthermore, studies have shown that when the silicon-aluminum ratio in the raw material is lower than 80, the characteristic diffraction peaks of ZSM-5 molecular sieves will be doped during the synthesis of ZSM-23 molecular sieves, affecting the purity of the product. When the silicon-aluminum ratio is in the range of 100 to 150, a pure phase ZSM-23 molecular sieve can be obtained. However, when the silicon-aluminum ratio exceeds 150, although the ZSM-23 molecular sieve is still the main product, diffraction peaks of impurities such as cristobalite begin to appear, which not only reduces the purity of the molecular sieve, but also may affect its catalytic performance.
[0005] On the other hand, although isopropylamine (IPA) can be used as a template to obtain products with better performance when synthesizing ZSM-23 molecular sieves, its application range is also limited. Specifically, when IPA is used as a template to synthesize ZSM-23 molecular sieves, the pure phase output of the molecular sieve can only be ensured within a narrow range of silicon-aluminum ratios of 160 to 250. This limitation means that the ZSM-23 molecular sieve synthesized by a single template lacks flexibility in regulating the silicon-aluminum ratio, which directly affects the physical and chemical properties of the molecular sieve, such as specific surface area and pore volume.
[0006] The above limitations indicate that the existing technology for synthesizing ZSM-23 zeolite is not only limited by the regulation range of the silicon-aluminum ratio, but also difficult to simultaneously optimize the pore properties of the zeolite, which poses a challenge to improving the catalytic performance of the zeolite and adapting it to a wider range of industrial applications. Summary of the invention
[0007] The main purpose of the present invention is to provide a ZSM-23 molecular sieve, a preparation method and application thereof, so as to solve the problem in the prior art that the ZSM-23 molecular sieve is difficult to achieve a wide silicon-to-aluminum ratio range, high purity and good pore properties.
[0008] In order to achieve the above-mentioned object, according to one aspect of the present invention, a method for preparing a ZSM-23 molecular sieve is provided. The raw materials include a silicon source, an aluminum source, a total template, an alkaline aqueous solution and a co-solvent, and the preparation method includes the following steps: step S1, mixing the raw materials to obtain a mixed gel; step S2, dynamically crystallizing the mixed gel to obtain a ZSM-23 molecular sieve; the total template is a mixture of pyrrolidine and isopropylamine, wherein the molar ratio of pyrrolidine and isopropylamine is (0.1-0.5): (0.1-0.3); or, the total template is a mixture of diethylamine and dimethylamine, wherein the molar ratio of diethylamine and dimethylamine is (0.1-0.3): (0.1-0.5); or, the total template is isobutylamine. A mixture of amine and N,N-dimethylformamide, wherein the molar ratio of isobutylamine to N,N-dimethylformamide is (0.1-0.4):(0.1-0.4); or, the total template agent is a mixture of isopropylamine, pyrrolidine and other template agents, wherein the molar ratio of isopropylamine, pyrrolidine and other template agents is (0.1-0.3):(0.1-0.3):(0.1-0.2), and other template agents include one or more of diethylamine, dimethylamine, isobutylamine and N,N-dimethylformamide; the co-solvent includes one or more of methanol, ethanol, ethylene glycol, propanol and isopropanol.
[0009] Further, when the total template agent is a mixture of pyrrolidine and isopropylamine, the co-solvent is ethanol; or, when the total template agent is a mixture of diethylamine and dimethylamine, the co-solvent is methanol; or, when the total template agent is a mixture of isobutylamine and N,N-dimethylformamide, the co-solvent is propanol; or, when the total template agent is a mixture of isopropylamine, pyrrolidine and other template agents, the co-solvent is methanol.
[0010] Furthermore, the molar ratio of the total template to the co-solvent is (0.1-0.8):(0.1-0.5).
[0011] Further, the silicon source includes one or more of silica sol, tetraethyl orthosilicate, fumed silica and water glass; and / or, the aluminum source includes one or more of pseudo-boehmite, aluminum sulfate, aluminum nitrate and sodium aluminate; and / or, the alkaline substance in the alkaline aqueous solution includes one or more of sodium hydroxide, potassium hydroxide and ammonia water; and / or, the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, the total template is expressed as R, and the alkaline aqueous solution is expressed as OH - The co-solvent is represented by Y. In terms of molar ratio, in the raw material, SiO2 / Al2O3=1:(0.004-0.03), R / SiO2=0.1-0.8, OH - / SiO2=0.01~0.2, Y / SiO2=0.01~0.5, H2O / SiO2=20~50.
[0012] Further, the silicon source is silica sol, the aluminum source is sodium aluminate, the alkaline substance in the alkaline aqueous solution is potassium hydroxide, the total template is a mixture of pyrrolidine and isopropylamine, and the co-solvent is ethanol; or, the silicon source is silica sol, the aluminum source is aluminum sulfate, the alkaline substance in the alkaline aqueous solution is sodium hydroxide, the total template is a mixture of diethylamine and dimethylamine, and the co-solvent is methanol; or, the silicon source is water glass, the aluminum source is aluminum nitrate, the alkaline substance in the alkaline aqueous solution is potassium hydroxide, the total template is a mixture of isobutylamine and N,N-dimethylformamide, and the co-solvent is propanol; or, the silicon source is silica sol, the aluminum source is pseudo-boehmite, the alkaline substance in the alkaline aqueous solution is sodium hydroxide, the total template is a mixture of isopropylamine, pyrrolidine and other templates, and the co-solvent is methanol.
[0013] Furthermore, the mixing process also includes the step of adding acid to control the pH of the mixed gel to be ≥10, preferably, controlling the pH of the mixed gel to be between 12 and 14; and / or, preferably, the acid includes one or more of hydrochloric acid, nitric acid, oxalic acid, citric acid and acetic acid.
[0014] Furthermore, the mixing includes: firstly mixing the silicon source, the aluminum source, the total template and the alkaline aqueous solution for a first time, then adding a co-solvent and performing a second time mixing to obtain a mixed gel. Preferably, the rotation speed of the first time mixing is 5 to 1000 rpm and the time is 10 to 150 min. Preferably, the rotation speed of the second time mixing is 5 to 1000 rpm and the time is 10 to 150 min.
[0015] Further, the dynamic crystallization includes: heating the mixed gel under stirring; preferably, the heating rate is 1 to 5°C / min; and / or, preferably, the stirring speed is 20 to 1000r / min; and / or, preferably, the end point temperature of the dynamic crystallization is 120 to 220°C, the time is 10 to 100h, and the pressure is 0.1 to 1MPa; more preferably, the end point temperature of the dynamic crystallization is 140 to 180°C, the time is 30 to 80h, and the pressure is 0.12 to 0.25MPa; and / or, preferably, the atmosphere of the dynamic crystallization is one or more of nitrogen, argon, helium and neon; and / or, the preparation method also includes the steps of sequentially performing solid-liquid separation, washing and drying on the ZSM-23 molecular sieve.
[0016] According to another aspect of the present invention, there is provided a ZSM-23 molecular sieve obtained according to the above preparation method.
[0017] According to another aspect of the present invention, there is provided an application of the above ZSM-23 molecular sieve.
[0018] By applying the technical solution of the present invention, adopting specific types of templates and co-solvents and adopting dynamic crystallization, multi-dimensional optimization in the preparation process of ZSM-23 molecular sieve is achieved, which not only broadens the control range of the silicon-aluminum ratio, but also significantly improves the pore properties and catalytic performance of the product molecular sieve, providing a more efficient and stable catalyst option for the field of industrial catalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0020] Figure 1 The XRD pattern of the ZSM-23 molecular sieve of Example 1 of the present invention is shown. DETAILED DESCRIPTION
[0021] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0022] As described in the background of the present invention, there is a problem in the prior art that ZSM-23 molecular sieves are difficult to balance a wide silicon-to-aluminum ratio range, high purity and good pore properties. In order to solve the above problems, in a typical embodiment of the present invention, a method for preparing a ZSM-23 molecular sieve is provided, wherein the raw materials include a silicon source, an aluminum source, a total template, an alkaline aqueous solution and a co-solvent, and the preparation method includes the following steps: Step S1, mixing the raw materials to obtain a mixed gel; Step S2, dynamically crystallizing the mixed gel to obtain a ZSM-23 molecular sieve; wherein the total template is a mixture of isopropylamine and pyrrolidine, and the total template is a mixture of pyrrolidine and isopropylamine, wherein the molar ratio of pyrrolidine and isopropylamine is (0.1 to 0.5): (0.1 to 0.3); or, the total template is a mixture of diethylamine and dimethylamine, wherein the molar ratio of diethylamine and dimethylamine is (0.1 to 0.5): (0.1 to 0.3). The ratio of isobutylamine to N,N-dimethylformamide is (0.1-0.3):(0.1-0.5); or, the total template agent is a mixture of isobutylamine and N,N-dimethylformamide, wherein the molar ratio of isobutylamine to N,N-dimethylformamide is (0.1-0.4):(0.1-0.4); or, the total template agent is a mixture of isopropylamine, pyrrolidine and other template agents, wherein the molar ratio of isopropylamine, pyrrolidine and other template agents is (0.1-0.3):(0.1-0.3):(0.1-0.2), and other template agents include one or more of diethylamine, dimethylamine, isobutylamine and N,N-dimethylformamide; the co-solvent includes one or more of methanol, ethanol, ethylene glycol, propanol and isopropanol.
[0023] The present application particularly adopts a total template agent of a specific combination, which acts as a structure-directing agent in the synthesis of ZSM-23 molecular sieves. They can be embedded in the crystallized structure of the framework precursor to guide the formation of the framework structure. Through the template-directing effect, the template agent can make the silicon source and the aluminum source form microcrystals with a specific geometric shape in the gel stage, thereby promoting the pure phase generation of ZSM-23 molecular sieves.
[0024] In particular, for the combination of isopropylamine IPA and pyrrolidine PY, due to the differences in their molecular size and spatial configuration, this combination can provide a clearly defined guiding framework for the directional growth of ZSM-23 crystal nuclei. IPA, with its larger molecular size, helps to form a stable gel structure and dominate the lattice construction, while PY plays a "spatial confinement" effect during the synthesis process, which can effectively regulate the pore size and distribution, optimize the pore properties and specific surface area of the molecular sieve, and significantly improve its catalytic conversion efficiency.
[0025] Similarly, the combination of diethylamine and dimethylamine, the combination of isobutylamine and N,N-dimethylformamide, and the combination of isopropylamine, pyrrolidine and other templates can also introduce a fine spatial confinement effect in the crystallization process of the ZSM-23 molecular sieve through their synergistic effect, and regulate the structural parameters of the molecular sieve to obtain a molecular sieve with a large specific surface area, pore volume and highly optimized micropore / mesopore specific volume distribution, which is beneficial to solving the technical problems of limited silicon-to-aluminum ratio and poor pore properties in traditional synthesis methods.
[0026] Secondly, the present application specifically defines the content of each component in the co-template, for example, when the total template is a mixture of isopropylamine and pyrrolidine, by accurately controlling the relative content of IPA and PY, it is not only possible to guide SiO2 and Al2O3 to be arranged in an orderly manner in the three-dimensional space under alkaline conditions to form the skeleton basis of the ZSM-23 molecular sieve, but also to further optimize its pore properties, achieve a significant increase in specific surface area and pore volume, thereby greatly enhancing the adsorption and catalytic performance of the molecular sieve. More importantly, the proportional balance between IPA and PY determines their competition and synergy mechanism in the molecular sieve synthesis process. Under this mechanism, the two templates can not only finely regulate the pore size and distribution of the ZSM-23 molecular sieve, ensuring that it exhibits excellent selectivity and diffusion performance in catalytic applications, but also effectively inhibit the generation of heterocrystalline phases such as ZSM-5, ensure the pure phase and stability of the molecular sieve, and effectively overcome the technical bottleneck of narrow silicon-aluminum ratio interval and unsatisfactory pore properties in the traditional preparation method.
[0027] However, if the content of pyrrolidine is too much, due to its large molecular weight and complex structure, it may occupy too much space, resulting in a larger pore size of the molecular sieve, affecting its shape-selective catalytic performance for small molecules, and may inhibit the guiding effect of IPA, resulting in the formation of heterocrystalline phases, such as the appearance of characteristic diffraction peaks of ZSM-5, thereby reducing the purity and selectivity of ZSM-23. On the contrary, if the content of isopropylamine is too much, due to the relatively simple molecular structure of IPA and the weak spatial confinement effect, it may not be able to effectively regulate the pore size of the molecular sieve, resulting in a small pore size or uneven pore distribution, affecting its diffusion performance and catalytic activity. At the same time, excessive IPA may not be able to form the best synergistic effect with PY, resulting in a decrease in the guiding ability of the template agent, which may cause a decrease in the crystallinity of the ZSM-23 molecular sieve or pore structure defects, thereby affecting its catalytic efficiency and stability. When the content of any template is too small, its guiding and confining effects will not be sufficient to compete and cooperate with the other template, which may lead to incomplete development of the molecular sieve structure, uneven grain size, and even failure to form a pure phase of ZSM-23 molecular sieve, reducing catalytic efficiency and increasing the possibility of side reactions.
[0028] When the total template is a mixture of other combinations, the mechanism is similar and will not be described in detail here.
[0029] At the same time, in the prior art, the solvent in the raw material is usually water. The inventors found that the solubility of the template in it is usually poor, and the present application specifically adds a specific type of co-solvent. The addition of a co-solvent can improve the uniformity of the mixed gel, enhance the dissolution and dispersion effect of the template, and further optimize the pore properties of the molecular sieve. The presence of a co-solvent can not only provide a more suitable dissolution environment for the template, but also may affect the formation process of the gel by changing the polarity and solvation environment of the system, so that the crystal can grow uniformly. This uniformity is crucial to ensure the high crystallinity and pure phase of the molecular sieve, which helps to avoid undesirable secondary reactions and reduce the generation of heterocrystalline phases. Compared with solvents in the prior art, such as water, the present application co-solvent has a higher polarity, can fully dissolve and disperse two or more templates, reduce the interfacial resistance between the ionic phase and the organic phase, accelerate the mass transfer between materials, and facilitate the rapid generation of grains.
[0030] In the present application, a specific type of total template and a specific type of co-solvent cooperate with each other to form a synergistic mechanism in the preparation process of the molecular sieve. The synergy between the template and the co-solvent is specifically embodied in that while the template guides the formation of skeleton crystallites, the co-solvent improves the solubility state of the template, which can ensure that the template can participate in the crystallization process more fully and evenly, and work together on the formation of gel and the growth of crystals, thereby improving the pure phase output rate and pore properties of the ZSM-23 molecular sieve.
[0031] In addition, the crystallization process of the present application is dynamic crystallization, which can avoid the uneven distribution of templates and crystal growth defects that may be caused by static crystallization, ensure the uniformity of the molecular sieve framework, and enhance the structural stability and pore uniformity of the molecular sieve.
[0032] In summary, this application achieves multi-dimensional optimization in the preparation process of ZSM-23 molecular sieve by adopting specific types of templates and co-solvents and using dynamic crystallization. It can not only broaden the control range of the silicon-aluminum ratio, but also significantly improve the pore properties and catalytic performance of the product molecular sieve, providing a more efficient and stable catalyst option for the field of industrial catalysis.
[0033] The inventor optimized the composition of the co-template and the co-solvent. In a preferred embodiment, when the total template is a mixture of pyrrolidine and isopropylamine, the co-solvent is ethanol; or, when the total template is a mixture of diethylamine and dimethylamine, the co-solvent is methanol; or, when the total template is a mixture of isobutylamine and N,N-dimethylformamide, the co-solvent is propanol; or, when the total template is a mixture of isopropylamine, pyrrolidine and other templates, the co-solvent is methanol. Under the above conditions, the co-template and the co-solvent are used in combination, which can more effectively improve the uniformity and specific surface area of the molecular sieve pores and improve the purity and crystallinity of the ZSM-23 molecular sieve by affecting the space and direction of crystal growth.
[0034] In a preferred embodiment, the molar ratio of the total template to the co-solvent is (0.1-0.8): (0.1-0.5). Under the above conditions, the dissolution and dispersion state of the template can be further optimized, and its uniform distribution in the gel system can be promoted, thereby regulating the orderly assembly of the molecular sieve framework, avoiding the formation of large particles and the appearance of heterocrystalline phases, significantly improving the purity and pore performance of the ZSM-23 molecular sieve, and enhancing its selectivity and activity in the catalytic reaction.
[0035] In order to further optimize the formation conditions of the gel and promote the efficient crystallization of the ZSM-23 molecular sieve, in a preferred embodiment, the silicon source includes one or more of silica sol, tetraethyl orthosilicate, fumed silica and water glass; and / or the aluminum source includes one or more of pseudo-boehmite, aluminum sulfate, aluminum nitrate and sodium aluminate; and / or the alkaline substance in the alkaline aqueous solution includes one or more of sodium hydroxide, potassium hydroxide and ammonia water.
[0036] In a preferred embodiment, the silicon source is represented by SiO2, the aluminum source is represented by Al2O3, the total template is represented by R, and the alkaline aqueous solution is represented by OH - The co-solvent is represented by Y. In terms of molar ratio, in the raw material, SiO2 / Al2O3=1:(0.004-0.03), R / SiO2=0.1-0.8, OH - / SiO2=0.01~0.2,Y / SiO2=0.01~0.5,H2O / SiO2=20~50. Under the above conditions, the components work together to further optimize the gel structure, promote the high-purity crystallization of ZSM-23 molecular sieve, effectively increase the micropore specific surface area and pore volume, and enhance the catalytic activity and selectivity.
[0037] In order to further improve the synthesis efficiency of ZSM-23 molecular sieve, in a preferred embodiment, the silicon source is silica sol, the aluminum source is sodium aluminate, the alkaline substance in the alkaline aqueous solution is potassium hydroxide, the total template is a mixture of pyrrolidine and isopropylamine, and the co-solvent is ethanol; or, the silicon source is silica sol, the aluminum source is aluminum sulfate, the alkaline substance in the alkaline aqueous solution is sodium hydroxide, the total template is a mixture of diethylamine and dimethylamine, and the co-solvent is methanol; or, the silicon source is water glass, the aluminum source is aluminum nitrate, the alkaline substance in the alkaline aqueous solution is potassium hydroxide, the total template is a mixture of isobutylamine and N,N-dimethylformamide, and the co-solvent is propanol; or, the silicon source is silica sol, the aluminum source is pseudo-boehmite, the alkaline substance in the alkaline aqueous solution is sodium hydroxide, the total template is a mixture of isopropylamine, pyrrolidine and other templates, and the co-solvent is methanol. Under the above conditions, not only can the pure phase of the product within a wide silicon-aluminum ratio range be ensured, but the micropore specific surface area and pore volume can also be greatly enhanced, thereby greatly improving the catalytic performance and selectivity of the molecular sieve.
[0038] In the prior art, the step of adjusting the pH of the mixed gel is usually not included, especially the use of acid solution for adjustment. The inventors found that the pH of the molecular sieve crystallization environment is an important factor affecting the growth of grains. Because the template agents in the system are all highly alkaline, too high alkalinity will accelerate the dissociation of silicon, accelerate the growth of the crystal nucleus, and the crystal growth is too fast, and the crystal crystallinity is not high. In order to optimize the crystallization process of the molecular sieve, in a preferred embodiment, the mixing also includes the step of adding acid solution to control the pH of the mixed gel ≥ 10, preferably, the pH of the mixed gel is controlled to 12-14; and / or, preferably, the acid solution includes one or more of hydrochloric acid, nitric acid, oxalic acid, citric acid and acetic acid. Under the above conditions, by adjusting the charge state of the system and the solubility of the species, the silicon source and the aluminum source are promoted to form a uniform and stable gel under alkaline conditions, so that the crystallization process of the molecular sieve can be further optimized, ensuring the high purity and good pore structure of the product, improving the specific surface area and pore volume of the ZSM-23 molecular sieve, and enhancing its activity and selectivity in the catalytic reaction.
[0039] In order to more effectively promote the uniform distribution of the template in the gel system, avoid the local concentration of the template being too high or too low, and ensure the orderly formation of the molecular sieve lattice in the subsequent crystallization process, in a preferred embodiment, the mixing includes: firstly mixing the silicon source, the aluminum source, the total template and the alkaline aqueous solution for a first time, and then adding a co-solvent to perform a second sub-mixing to obtain a mixed gel. Preferably, the rotation speed of the first sub-mixing is 5 to 1000 rpm and the time is 10 to 150 min. Preferably, the rotation speed of the second sub-mixing is 5 to 1000 rpm and the time is 10 to 150 min.
[0040] The inventors optimized the parameters of crystallization temperature, pressure and atmosphere. In a preferred embodiment, dynamic crystallization includes: heating the mixed gel under stirring; preferably, the heating rate is 1-5°C / min; and / or, preferably, the stirring speed is 20-1000r / min; and / or, preferably, the end temperature of dynamic crystallization is 120-220°C, the time is 10-100h, and the pressure is 0.1-1MPa; more preferably, the end temperature of dynamic crystallization is 140-180°C, the time is 30-80h, and the pressure is 0.12-0.25MPa; and / or, preferably, the atmosphere of dynamic crystallization is one or more of nitrogen, argon, helium and neon. Under the above conditions, the rate and direction of crystal growth can be more effectively adjusted, while effectively preventing excessive aggregation of grains and the formation of heterocrystalline phases, reducing crystal defects, and improving the crystallinity and purity of molecular sieves.
[0041] It should be noted that the pressure of the dynamic crystallization of the present application is 0.1-1 MPa, preferably 0.12-0.25 MPa. Within this range, the relative balance of the liquid phase components in the system is controlled by the system pressure, and the effective solubility of low-boiling point components such as co-solvents is ensured, which is more conducive to coordinating the synergistic effect between the templates, promoting the directional formation of crystals, and improving the pore structure. In addition, the atmosphere of the dynamic crystallization of the present application is an inert atmosphere or a nitrogen atmosphere. Under this condition, the impact on the system environment is small.
[0042] In a preferred embodiment, the preparation method also includes the steps of sequentially performing solid-liquid separation, washing and drying of the ZSM-23 molecular sieve. The ZSM-23 molecular sieve is subjected to solid-liquid separation to effectively remove unreacted raw materials and by-products, and washing further removes gel residues and reaction by-products to prevent them from becoming impurities or blocking pores during subsequent drying and template removal; drying ensures that the molecular sieve structure is stable, prevents structural collapse caused by residual moisture or incomplete decomposition of the template agent, and the whole process synergistically can significantly improve the purity and pore structure integrity of the molecular sieve, and has a positive promoting effect on its catalytic activity and stability.
[0043] In another typical embodiment of the present invention, a ZSM-23 molecular sieve is also provided, obtained according to the above preparation method. Through the control of synergistic effect, the present application can realize the preparation of ZSM-23 molecular sieve in a wider silicon-aluminum ratio range (such as 60-200), break the limitation of single template synthesis on silicon-aluminum ratio, and broaden the optimization space of the physicochemical properties of molecular sieve. More importantly, the optimized micropore specific surface area and micropore volume, as well as higher crystallinity, can significantly improve the catalytic activity and selectivity of ZSM-23 molecular sieve. Compared with the prior art, the ZSM-23 molecular sieve prepared in the present application has more excellent pore properties while maintaining high purity, which not only has a positive effect on the catalytic reaction rate and selectivity, but also may reduce the deactivation rate of the catalyst and extend its service life.
[0044] In another typical embodiment of the present invention, the application of the above-mentioned ZSM-23 molecular sieve in the field of catalytic methanol to olefins, light oil cracking, selective alkylation of alkylbenzenes, and isomerization decondensation is also provided. As mentioned above, the molecular sieve preparation method of the present application can effectively expand the silicon-aluminum ratio range of the ZSM-23 molecular sieve through the synergistic effect of the dual template agent and the optimized dynamic crystallization conditions, and improve its micropore specific surface area and pore volume, thereby enhancing the activity, selectivity and stability of the molecular sieve in the application of catalytic methanol to olefins, light oil cracking, selective alkylation of alkylbenzenes, and isomerization decondensation, and broaden its application prospects in the fields of fine chemicals, petroleum refining and environmental protection catalysis.
[0045] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0046] Example 1
[0047] The raw materials of ZSM-23 molecular sieve include silicon source (silica sol), aluminum source (Al2(SO4)3·18H2O), template (pyrrolidine PY, isopropylamine IPA), alkaline aqueous solution (KOH), co-solvent (ethanol) and deionized water, in molar ratio, SiO2:Al2O3:PY:IPA:OH - :Y:H2O=1:0.007:0.4:0.1:0.1:0.1:40.
[0048] Step S1, adding a silicon source, an aluminum source and a total template agent to an alkaline aqueous solution, stirring at a rotation speed of 500 rpm for 60 minutes, then adding a co-solvent, continuing to stir at a rotation speed of 500 rpm for 10 minutes, then adding hydrochloric acid, adjusting the pH value of the mixed solution to 13, and obtaining a mixed gel;
[0049] Step S2, the mixed gel is quickly transferred into a high pressure reactor, and crystallized for 72 hours at a speed of 50 rpm, a heating rate of 1.5 ° C / min, a temperature of 180 ° C, a pressure of 0.3 MPa, and a nitrogen atmosphere, and solid-liquid separation, washing and drying are performed at 25 ° C to obtain a ZSM-23 molecular sieve. The XRD pattern of the ZSM-23 molecular sieve is shown in Figure 1 This was used as a standard sample, and the crystallinity was 100%.
[0050] The ZSM-23 molecular sieve was calcined at 350°C for 5h to remove the template agent, and the obtained product was subjected to ion exchange with a 1 mol / L ammonium chloride aqueous solution (temperature: 80°C, time: 3h), and the ion exchange was repeated 3 times. The obtained product was separated by filtration and dried, and then calcined at 550°C for 10h in an air atmosphere to obtain the H-ZSM-23 molecular sieve; the H-ZSM-23 molecular sieve was mixed with pseudo-boehmite in a weight ratio of 7:3, and then nitric acid solution was added to bond, and extruded into strips. The obtained molded product was calcined at 550°C for 4h in an air atmosphere to obtain the H-ZSM-23 molecular sieve carrier; the chloroplatinic acid aqueous solution and the H-ZSM-23 molecular sieve carrier were stirred and impregnated at 25°C for 24h, the impregnated product was dried in an oven at 110°C for 3h, and then calcined at 400°C for 4h to obtain the H-ZSM-23 molecular sieve catalyst. Wherein, based on the total weight of the H-ZSM-23 molecular sieve catalyst, the content of Pt is 0.5 wt%.
[0051] The H-ZSM-23 molecular sieve catalyst was crushed into 20-40 meshes, 20 mL of H-ZSM-23 molecular sieve catalyst was loaded into the constant temperature zone of the reaction tube, and the catalyst in the reaction tube was supported by inert quartz sand.
[0052] The catalyst was used to carry out catalytic dewaxing and pour point reduction experiments on Fischer-Tropsch synthetic wax oil. The process conditions evaluated were as follows: hydrogen partial pressure 3.5 MPa, volume space velocity 1.0 h -1 , hydrogen-oil volume ratio 500:1, reaction temperature 360°C.
[0053] Example 2
[0054] The only difference from Example 1 is:
[0055] The raw materials of ZSM-23 molecular sieve include silicon source (silica sol), aluminum source (Al2(SO4)3·18H2O), template (pyrrolidine PY, isopropylamine IPA), alkaline aqueous solution (KOH), co-solvent (ethanol) and deionized water, in molar ratio, SiO2:Al2O3:PY:IPA:OH - :Y:H2O=1:0.007:0.3:0.2:0.1:0.1:40.
[0056] Example 3
[0057] The only difference from Example 1 is:
[0058] The raw materials of ZSM-23 molecular sieve include silicon source (silica sol), aluminum source (Al2(SO4)3·18H2O), template (pyrrolidine PY, isopropylamine IPA), alkaline aqueous solution (KOH), co-solvent (ethanol) and deionized water, in molar ratio, SiO2:Al2O3:PY:IPA:OH - :Y:H2O=1:0.007:0.2:0.3:0.1:0.1:40.
[0059] Example 4
[0060] The only difference from Example 1 is:
[0061] The raw materials of ZSM-23 molecular sieve include silicon source (silica sol), aluminum source (Al2(SO4)3·18H2O), template (pyrrolidine PY, isopropylamine IPA), alkaline aqueous solution (KOH), co-solvent (ethanol) and deionized water, in molar ratio, SiO2:Al2O3:PY:IPA:OH - :Y:H2O=1:0.007:0.4:0.1:0.1:0.1:40.
[0062] Example 5
[0063] The only difference from Example 1 is:
[0064] The raw materials of ZSM-23 molecular sieve include silicon source (silica sol), aluminum source (Al2(SO4)3·18H2O), template (diethylamine and dimethylamine), alkaline aqueous solution (NaOH), co-solvent (methanol) and deionized water, in molar ratio, SiO2:Al2O3:diethylamine:dimethylamine:OH - :Y:H2O=1:0.007:0.2:0.2:0.1:0.1:40.
[0065] Step S1, adding a silicon source, an aluminum source and a total template agent to an alkaline aqueous solution, stirring at a rotation speed of 500 rpm for 60 minutes, then adding a co-solvent, continuing to stir at a rotation speed of 500 rpm for 10 minutes, and then adding hydrochloric acid to adjust the pH value of the mixed solution to 14 to obtain a mixed gel;
[0066] Step S2, the mixed gel is quickly transferred into a high-pressure reactor, crystallized for 72 hours at a rotation speed of 50 rpm, a heating rate of 1.5°C / min, a temperature of 180°C, a pressure of 0.3 MPa, and a nitrogen atmosphere, and solid-liquid separation, washing and drying are performed at 25°C to obtain a ZSM-23 molecular sieve.
[0067] Example 6
[0068] The only difference from Example 1 is:
[0069] The raw materials of ZSM-23 molecular sieve include silicon source (silica sol), aluminum source (Al2(SO4)3·18H2O), template (isobutylamine and N,N-dimethylformamide), alkaline aqueous solution (NaOH), co-solvent (propanol) and deionized water, in molar ratio, SiO2:Al2O3:isobutylamine:N,N-dimethylformamide:OH - :Y:H2O=1:0.007:0.2:0.2:0.1:0.1:40.
[0070] Step S1, adding a silicon source, an aluminum source and a total template agent to an alkaline aqueous solution, stirring at a rotation speed of 500 rpm for 60 minutes, then adding a co-solvent, continuing to stir at a rotation speed of 500 rpm for 10 minutes, and then adding hydrochloric acid to adjust the pH value of the mixed solution to 14 to obtain a mixed gel;
[0071] Step S2, the mixed gel is quickly transferred into a high-pressure reactor, crystallized for 72 hours at a rotation speed of 50 rpm, a heating rate of 1.5°C / min, a temperature of 180°C, a pressure of 0.3 MPa, and a nitrogen atmosphere, and solid-liquid separation, washing and drying are performed at 25°C to obtain a ZSM-23 molecular sieve.
[0072] Example 7
[0073] The only difference from Example 1 is:
[0074] The raw materials of ZSM-23 molecular sieve include silicon source (silica sol), aluminum source (Al2(SO4)3·18H2O), template (isopropylamine, pyrrolidine), alkaline aqueous solution (NaOH), co-solvent (ethanol) and deionized water, in molar ratio, SiO2:Al2O3:PY:IPA:OH - :Y:H2O=1:0.007:0.2:0.2:0.1:0.1:0.1:35.
[0075] Step S1, adding a silicon source, an aluminum source and a total template agent to an alkaline aqueous solution, stirring at a rotation speed of 500 rpm for 60 minutes, then adding a co-solvent, continuing to stir at a rotation speed of 500 rpm for 10 minutes, and then adding hydrochloric acid to adjust the pH value of the mixed solution to 14 to obtain a mixed gel;
[0076] Step S2, the mixed gel is quickly transferred into a high-pressure reactor, crystallized for 72 hours at a rotation speed of 50 rpm, a heating rate of 1.5°C / min, a temperature of 180°C, a pressure of 0.3 MPa, and a nitrogen atmosphere, and solid-liquid separation, washing and drying are performed at 25°C to obtain a ZSM-23 molecular sieve.
[0077] Example 8
[0078] The only difference from Example 1 is:
[0079] The raw materials of ZSM-23 molecular sieve include silicon source (silica sol), aluminum source (Al2(SO4)3·18H2O), template (pyrrolidine PY, isopropylamine IPA, dimethylamine), alkaline aqueous solution (KOH), co-solvent (ethanol) and deionized water, in molar ratio, SiO2:Al2O3:PY:IPA:dimethylamine:OH - :Y:H2O=1:0.007:0.1:0.1:0.1:0.1:0.1:40.
[0080] Step S1, adding a silicon source, an aluminum source and a total template agent to an alkaline aqueous solution, stirring at a rotation speed of 500 rpm for 60 minutes, then adding a co-solvent, continuing to stir at a rotation speed of 500 rpm for 10 minutes, then adding hydrochloric acid, adjusting the pH value of the mixed solution to 13, and obtaining a mixed gel;
[0081] Step S2, the mixed gel is quickly transferred into a high-pressure reactor, crystallized for 72 hours at a rotation speed of 50 rpm, a heating rate of 1.5°C / min, a temperature of 180°C, a pressure of 0.3 MPa, and a nitrogen atmosphere, and solid-liquid separation, washing and drying are performed at 25°C to obtain a ZSM-23 molecular sieve.
[0082] Example 9
[0083] The only difference from Example 1 is:
[0084] The raw materials of ZSM-23 molecular sieve include silicon source (silica sol), aluminum source (Al2(SO4)3·18H2O), template (pyrrolidine PY, isopropylamine IPA), alkaline aqueous solution (KOH), co-solvent (ethanol) and deionized water, in molar ratio, SiO2:Al2O3:PY:IPA:OH - :Y:H2O=1:0.007:0.4:0.1:0.1:0.1:40.
[0085] Step S1, adding a silicon source, an aluminum source and a total template agent to an alkaline aqueous solution, stirring at a rotation speed of 500 rpm for 60 minutes, then adding a co-solvent, continuing to stir at a rotation speed of 500 rpm for 10 minutes, then adding hydrochloric acid, adjusting the pH value of the mixed solution to 13, and obtaining a mixed gel;
[0086] Step S2, the mixed gel is quickly transferred into a high-pressure reactor, crystallized for 60 hours at a rotation speed of 50 rpm, a heating rate of 1.5°C / min, a temperature of 180°C, a pressure of 0.3 MPa, and a nitrogen atmosphere, and solid-liquid separation, washing and drying are performed at 25°C to obtain a ZSM-23 molecular sieve.
[0087] Example 10
[0088] The only difference from Example 1 is:
[0089] The raw materials of ZSM-23 molecular sieve include silicon source (silica sol), aluminum source (Al2(SO4)3·18H2O), template (pyrrolidine PY, isopropylamine IPA), alkaline aqueous solution (KOH), co-solvent (ethanol) and deionized water, in molar ratio, SiO2:Al2O3:PY:IPA:OH - :Y:H2O=1:0.007:0.4:0.1:0.1:0.1:40.
[0090] Step S1, adding a silicon source, an aluminum source and a total template agent to an alkaline aqueous solution, stirring at a rotation speed of 500 rpm for 60 minutes, then adding a co-solvent, continuing to stir at a rotation speed of 500 rpm for 10 minutes, then adding hydrochloric acid, adjusting the pH value of the mixed solution to 13, and obtaining a mixed gel;
[0091] Step S2, the mixed gel is quickly transferred into a high-pressure reactor, crystallized for 72 hours at a rotation speed of 50 rpm, a heating rate of 1.5°C / min, a temperature of 160°C, a pressure of 0.3 MPa, and a nitrogen atmosphere, and solid-liquid separation, washing and drying are performed at 25°C to obtain a ZSM-23 molecular sieve.
[0092] Embodiment 11
[0093] The only difference from Example 1 is:
[0094] The raw materials of ZSM-23 molecular sieve include silicon source (silica sol), aluminum source (Al2(SO4)3·18H2O), template (pyrrolidine PY, isopropylamine IPA), alkaline aqueous solution (KOH), co-solvent (ethanol) and deionized water, in molar ratio, SiO2:Al2O3:PY:IPA:OH - :Y:H2O=1:0.007:0.4:0.1:0.1:0.1:25.
[0095] Example 12
[0096] The only difference from Example 1 is:
[0097] The raw materials of ZSM-23 molecular sieve include silicon source (silica sol), aluminum source (Al2(SO4)3·18H2O), template (pyrrolidine PY, isopropylamine IPA), alkaline aqueous solution (KOH), co-solvent (ethanol) and deionized water, in molar ratio, SiO2:Al2O3:PY:IPA:OH - :Y:H2O=1:0.007:0.4:0.1:0.1:0.1:50.
[0098] Comparative Example 1
[0099] The only difference from Example 7 is that the template is of a single type, namely, pyrrolidine. In the mixed gel, in terms of molar ratio, SiO2:Al2O3:PY:OH - :Y:H2O=1:0.007:0.4:0.1:0.1:40.
[0100] It can be seen from the analysis that compared with the comparative example, Example 7 uses two templates to synergistically guide the formation of crystals. Due to the differences in molecular size and spatial shape of PA and PY, primary and secondary guiding structures are provided for the directional growth of crystal nuclei during the crystallization of the molecular sieve, which can work synergistically. Since part of PY plays the role of "spatial confinement" during the synthesis process, the generated molecular sieve has a small grain size and a large specific surface area. At the same time, the crystallinity of the target molecular sieve is relatively high, and the product yield is high. However, Comparative Example 1 uses a single template, which fails to play a synergistic guiding role in the molecular sieve crystallization process, and the molecular sieve pore properties deteriorate.
[0101] Comparative Example 2
[0102] The only difference from Example 7 is that the template is of a single type, which only includes pyrrolidine. In the mixed gel, in terms of molar ratio, SiO2:Al2O3:IPA:OH - :Y:H2O=1:0.007:0.4:0.1:0.1:40.
[0103] After analysis, it can be known that compared with the comparative example, Example 7 uses two templates to synergistically guide the formation of crystals. Due to the differences in molecular size and spatial shape of PA and PY, they provide primary and secondary guiding structures for the directional growth of crystal nuclei during the crystallization process of the molecular sieve, which can work synergistically to make the generated molecular sieve have a small grain size and a large specific surface area. At the same time, the crystallinity of the target molecular sieve is relatively high, and the product yield is high. Comparative Example 2 uses a single template, which fails to play a synergistic guiding role in the crystallization process of the molecular sieve, and the pore properties of the molecular sieve deteriorate.
[0104] Comparative Example 3
[0105] The only difference from Example 7 is that in the mixed gel, in molar ratio, SiO2:Al2O3:PY:IPA:OH- :Y:H2O=1:0.007:0.4:0.5:0.1:0.1:40, co-solvent is ethanol.
[0106] It can be seen from the analysis that, compared with the comparative example, Example 7 reasonably controls the proportion of the template in the raw material ratio, so that the molecular sieve grows in an orderly manner during the crystallization process, and the molecular sieve product has a high crystallinity and a good pore structure under the isomorphous condition. In Comparative Example 3, the proportion of the template added is too high, which causes a change in the crystallization process. Under the isomorphous condition, the molecular sieve is prone to overgrowth, and the crystallinity and pore structure change significantly.
[0107] Comparative Example 4
[0108] The only difference from Example 1 is that in the mixed gel, in molar ratio, SiO2:Al2O3:PY:IPA:OH - :Y:H2O=1:0.007:0.05:0.05:0.1:0.1:40, co-solvent is ethanol.
[0109] The analysis shows that in Comparative Example 4, the proportion of template added is too low, the molecular sieve growth structure is insufficient, and under isomorphous conditions, the molecular sieve grows slowly, has low crystallinity, and has a low product yield.
[0110] Comparative Example 5
[0111] The only difference from Example 1 is that the pressure of dynamic crystallization is 0.05 MPa and the atmosphere is air.
[0112] According to the analysis, in Comparative Example 5, the system pressure is low, the saturated vapor pressure of the co-solvent is small, and the effective solubility of the co-solvent is low, which is not conducive to the coordination of the synergistic effect between the templates, the directional formation of crystals, and the improvement of the pore structure. In addition, under the condition of air gas atmosphere, a certain oxidative side effect is produced on the organic solvent components such as the co-solvent, which reduces the content of the organic components.
[0113] Comparative Example 6
[0114] The only difference from Example 1 is that the co-solvent is water.
[0115] The analysis shows that in Comparative Example 6, the addition of blank co-solvent "water" reduces the dissolution and dispersion effects of the template, and the polarity and solvation environment of the system deteriorate, which affects the gel formation process and is not conducive to the formation of crystals.
[0116] Comparative Example 7
[0117] The only difference from Example 1 is that a single template is used and no acid is added for adjustment. Specifically,
[0118] The raw materials of ZSM-23 molecular sieve include silicon source (silica sol), aluminum source (Al2(SO4)3·18H2O), template (pyrrolidine PY), alkaline aqueous solution (KOH), co-solvent (ethanol) and deionized water, in molar ratio, SiO2:Al2O3:PY:OH - :Y:H2O=1:0.007:0.5:0.1:0.1:40.
[0119] Step S1, adding a silicon source, an aluminum source and a total template agent to an alkaline aqueous solution, stirring at a rotation speed of 500 rpm for 60 minutes, then adding a co-solvent, and continuing to stir at a rotation speed of 500 rpm for 10 minutes to obtain a mixed gel;
[0120] Step S2, the mixed gel is quickly transferred into a high-pressure reactor, crystallized for 72 hours at a rotation speed of 50 rpm, a heating rate of 1.5°C / min, and a temperature of 180°C, and solid-liquid separation, washing and drying are performed at 25°C to obtain a ZSM-23 molecular sieve.
[0121] The test results of the ZSM-23 molecular sieve obtained in the above examples and comparative examples are shown in Table 1, the properties of the Fischer-Tropsch wax oil are shown in Table 2, and the test results of the pour point, viscosity index and liquid yield of the lubricating oil base oil product after the reaction are shown in Table 3.
[0122] Test method:
[0123] Crystallinity test: The crystallinity parameters were measured by X-ray diffraction (XRD) method. The specific test conditions were: using PANalytical X'pert3 powder from the Netherlands, working voltage of 40 kV, tube current of 40 mA, copper target, 1D semiconductor PIXcel1D matrix detector, scanning mode: θ / θ, minimum step length: 0.0001. The sample to be tested was dried, ground, and pressed into tablets. The diffraction intensity (peak height) of the characteristic peaks of the standard sample and the sample to be tested was measured by X-ray diffractometer to obtain the relative crystallinity of the sample to be tested RC = (ΣI sample / ΣI standard) × 100%.
[0124] Grain size test: In the present invention, unless otherwise specified, the grain size parameters are measured using the SEM electron microscope method; specific test conditions: the test is carried out using a Phenom-Pro scanning electron microscope from the Netherlands, the sample is fully ground and then the surface is gold-sprayed, and the acceleration voltage is 20 kV.
[0125] Pore structure test: The pore structure and specific surface area of the sample were completed on the ASAP2420 surface analyzer. The chemical pulse adsorption method was used to measure and record the desorption area of the sample after adsorbing nitrogen at liquid nitrogen temperature. The sample was pretreated at 350°C for 8 hours before the measurement. The specific surface area and pore volume of the sample were simulated and calculated using the t-plot model, and the pore size distribution of the sample was calculated using the BJH model.
[0126] Viscosity index: measured according to ASTM D2270 (GB / T 1995-1998) using an SMV3000 instrument from Anton Paar, Austria.
[0127] Pour point: measured according to GB / T 3535-2006 method using HP850C instrument from Heilchau, Germany.
[0128] The calculation formula for liquid yield is: Liquid yield = (350°C ~ FBP) liquid product weight / incoming raw material weight × 100%.
[0129] Table 1
[0130]
[0131]
[0132] Table 2
[0133]
[0134] Table 3
[0135]
[0136]
[0137] It can be seen from the above that, compared with the comparative example, the molecular sieve prepared by the method of the present invention is used for Fischer-Tropsch wax pour point reduction, which is beneficial to improving the liquid yield of the lubricating oil base oil and the viscosity index of the product, and reducing the pour point of the base oil.
[0138] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a ZSM-23 molecular sieve, characterized in that: The raw materials include a silicon source, an aluminum source, a total template, an alkaline aqueous solution and a co-solvent. The preparation method includes the following steps: Step S1, mixing the raw materials to obtain a mixed gel; Step S2, dynamically crystallizing the mixed gel to obtain the ZSM-23 molecular sieve; The total template agent is a mixture of pyrrolidine and isopropylamine, wherein the molar ratio of pyrrolidine to isopropylamine is (0.1-0.5):(0.1-0.3); Alternatively, the total template agent is a mixture of diethylamine and dimethylamine, wherein the molar ratio of diethylamine to dimethylamine is (0.1-0.3):(0.1-0.5); Alternatively, the total template agent is a mixture of isobutylamine and N,N-dimethylformamide, wherein the molar ratio of isobutylamine to N,N-dimethylformamide is (0.1-0.4):(0.1-0.4); Alternatively, the total template agent is a mixture of isopropylamine, pyrrolidine and other template agents, wherein the molar ratio of isopropylamine, pyrrolidine and the other template agents is (0.1-0.3):(0.1-0.3):(0.1-0.2), and the other template agents include one or more of diethylamine, dimethylamine, isobutylamine and N,N-dimethylformamide; The co-solvent includes one or more of methanol, ethanol, ethylene glycol, propanol and isopropanol.
2. The preparation method according to claim 1, characterized in that: When the total template is a mixture of pyrrolidine and isopropylamine, the co-solvent is ethanol; Alternatively, when the total template is a mixture of diethylamine and dimethylamine, the co-solvent is methanol; Alternatively, when the total template is a mixture of isobutylamine and N,N-dimethylformamide, the co-solvent is propanol; Alternatively, when the total template is a mixture of isopropylamine, pyrrolidine and the other templates, the co-solvent is methanol.
3. The preparation method according to claim 1 or 2, characterized in that: The molar ratio of the total template to the co-solvent is (0.1-0.8):(0.1-0.5).
4. The preparation method according to any one of claims 1 to 3, characterized in that The silicon source includes one or more of silica sol, tetraethyl orthosilicate, fumed silica and water glass; and / or, The aluminum source includes one or more of pseudo-boehmite, aluminum sulfate, aluminum nitrate and sodium aluminate; and / or, The alkaline substance in the alkaline aqueous solution includes one or more of sodium hydroxide, potassium hydroxide and ammonia water; and / or, The silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, the total template is expressed as R, the alkaline aqueous solution is expressed as OH-, and the co-solvent is expressed as Y. In terms of molar ratio, in the raw material, SiO2 / Al2O3=1:(0.004-0.03), R / SiO2=0.1-0.8, OH - / SiO2=0.01~0.2, Y / SiO2=0.01~0.5, H2O / SiO2=20~50.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The silicon source is silica sol, the aluminum source is sodium metaaluminate, the alkaline substance in the alkaline aqueous solution is potassium hydroxide, the total template agent is a mixture of pyrrolidine and isopropylamine, and the co-solvent is ethanol; Alternatively, the silicon source is silica sol, the aluminum source is aluminum sulfate, the alkaline substance in the alkaline aqueous solution is sodium hydroxide, the total template agent is a mixture of diethylamine and dimethylamine, and the co-solvent is methanol; Alternatively, the silicon source is water glass, the aluminum source is aluminum nitrate, the alkaline substance in the alkaline aqueous solution is potassium hydroxide, the total template agent is a mixture of isobutylamine and N,N-dimethylformamide, and the co-solvent is propanol; Alternatively, the silicon source is silica sol, the aluminum source is pseudo-boehmite, the alkaline substance in the alkaline aqueous solution is sodium hydroxide, the total template agent is a mixture of isopropylamine, pyrrolidine and the other template agents, and the co-solvent is methanol.
6. The preparation method according to any one of claims 1 to 5, characterized in that The mixing process also includes adding acid to control the pH of the mixed gel to be ≥10. Preferably, the pH of the mixed gel is controlled to be between 12 and 14; and / or, Preferably, the acid solution comprises one or more of hydrochloric acid, nitric acid, oxalic acid, citric acid and acetic acid.
7. The preparation method according to any one of claims 1 to 6, characterized in that The mixing comprises: firstly mixing the silicon source, the aluminum source, the total template and the alkaline aqueous solution, and then adding the co-solvent to perform a second mixing to obtain the mixed gel. Preferably, the first submixing is performed at a speed of 5 to 1000 rpm for a time of 10 to 150 min. Preferably, the second submixing has a rotation speed of 5 to 1000 rpm and a mixing time of 10 to 150 min.
8. The preparation method according to any one of claims 1 to 7, characterized in that The dynamic crystallization comprises: heating the mixed gel under stirring; Preferably, the heating rate is 1-5°C / min; and / or, Preferably, the stirring speed is 20 to 1000 r / min; and / or, Preferably, the end point temperature of the dynamic crystallization is 120-220° C., the time is 10-100 h, and the pressure is 0.1-1 MPa; more preferably, the end point temperature of the dynamic crystallization is 140-180° C., the time is 30-80 h, and the pressure is 0.12-0.25 MPa; and / or, Preferably, the atmosphere of the dynamic crystallization is one or more of nitrogen, argon, helium and neon; and / or, The preparation method also includes the steps of sequentially performing solid-liquid separation, washing and drying on the ZSM-23 molecular sieve.
9. A ZSM-23 molecular sieve, characterized in that: Obtained according to the preparation method according to any one of claims 1 to 8.
10. Use of the ZSM-23 molecular sieve according to claim 9 in the fields of catalytic methanol to olefins, light oil cracking, alkylbenzene selective alkylation, and isomerization decondensation.
Citation Information
Patent Citations
Synthesis of ZSM-23 zeolite
US4490342A
Synthesis of ZSM-23 zeolite and the product produced
US4619820A
Process for preparing zeolites having MTT crystal structure using small, neutral amines
US5707601A